2022
DOI: 10.12681/mms.29712
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a new research tool for evaluating Mediterranean Sea Literacy (MSL) of high school students: A pilot study

Abstract: The Mediterranean Sea is recognized as a key component in the development, economy, and culture of European, North African, and Middle East countries. With respect to heterogeneity across the region in different sectors, Ocean Literacy, though still in its infancy, is nevertheless a requisite for a better understanding of the two-way interaction between the Sea and its people. In the present study, marine issues in relation to the content knowledge of 154 high school students from the Mediterranean region were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Low et al ( 2013) investigated misconceptions about marine sciences presented by Taiwanese students and identified that they had moderate knowledge, with an average rate of correct answers about marine concepts of 50%. Cheimonopoulou et al (2022) assessed the knowledge about marine issues of students from the Mediterranean region of Italy and Greece and identified a rate of 40% correct answers for questions related to marine concepts. Unlike the first two studies, Chang, Tsai, and Meliana (2023) assessed the OL level of students at an Indonesian maritime vocational school that presents a curriculum focused on the marine environment and obtained 70% correct answers on marine issues and concluded that, in this case, students have a basic level OL.…”
Section: Ementioning
confidence: 99%
“…Low et al ( 2013) investigated misconceptions about marine sciences presented by Taiwanese students and identified that they had moderate knowledge, with an average rate of correct answers about marine concepts of 50%. Cheimonopoulou et al (2022) assessed the knowledge about marine issues of students from the Mediterranean region of Italy and Greece and identified a rate of 40% correct answers for questions related to marine concepts. Unlike the first two studies, Chang, Tsai, and Meliana (2023) assessed the OL level of students at an Indonesian maritime vocational school that presents a curriculum focused on the marine environment and obtained 70% correct answers on marine issues and concluded that, in this case, students have a basic level OL.…”
Section: Ementioning
confidence: 99%
“…Furthermore, the Intergovernmental Oceanographic Commission of UNESCO (IOC-UNESCO) is currently developing the Ocean Literacy Strategy -Ocean Literacy for the UN Decade of Ocean Science for Sustainable Development -in order to advance OL during the UN Decade. In this context, the Mediterranean Sea is considered to be a key component in the development, economy, and culture of European, North African, and Asian countries as well as an agent for the "transformative change" that needs to be achieved for a sustainable future in this region (Cheimonopoulou et al, 2022).…”
mentioning
confidence: 99%
“…Koulouri et al (2022) study OL issues in relation to content knowledge, misconceptions, attitudes, and behaviour of junior high school students from eight Mediterranean countries. In parallel, a pilot survey carried out among Mediterranean high school students using for the first time a research tool based on the newly launched Mediterranean Sea Literacy guide is investigated by Cheimonopoulou et al (2022). A short description of OL research and activities across the Mediterranean Sea region is also presented.…”
mentioning
confidence: 99%